2017
DOI: 10.1016/j.actatropica.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insecticide-treated bed nets on house-entry by malaria mosquitoes: The flight response recorded in a semi-field study in Kenya

Abstract: Insecticide-treated nets are currently a major tool to reduce malaria transmission. Their level of repellency affects contact of the mosquito with the net, but may also influence the mosquito's entry into the house. The response of host-seeking malaria mosquitoes approaching the eave of an experimental house was recorded within a large screen house. We compared entry- and exit rates in relation to the presence in the house of different insecticide-treated bed nets (ITNs) with an untreated net. Mosquitoes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…No volatile or pre-contact repellent effects of the LLINs had been observed in either study, suggesting that observed behaviours were responses by mosquitoes after LLIN contact. This is supported by a recent report that LLINs did not affect house entry rates [66]. A limitation of our study was that the closed test room design prevented the detection of exiting behaviour following net contact.…”
Section: Discussionsupporting
confidence: 50%
“…No volatile or pre-contact repellent effects of the LLINs had been observed in either study, suggesting that observed behaviours were responses by mosquitoes after LLIN contact. This is supported by a recent report that LLINs did not affect house entry rates [66]. A limitation of our study was that the closed test room design prevented the detection of exiting behaviour following net contact.…”
Section: Discussionsupporting
confidence: 50%
“…Mosquitoes exposed to permethrin will not seek a blood meal even under these conditions because of a loss of the ability to sense host cues. Similarly, the deterrence will be beneficial for persons who are not under an LLIN [56,57]. Further, this effect may reduce early-hour biting activity in the room or even outdoor biting activity near a house with an Olyset ® [8].…”
Section: Discussionmentioning
confidence: 99%
“…One method for reducing mosquito contacts with humans is to disrupt the mosquito -host interaction with the use of bed nets. Because CO 2 , volatile skin chemicals, heat and moisture plumes readily pass through net meshing, bed nets interfere with neither the initial long-range search phase nor the identification and approach portion of the second short-range phase (spatial repellency effects of insecticide-treated nets are observed to be weak or non-existent) [36,37]. Bed nets do, however, interfere with the landing portion of short-range phase by physically blocking mosquitoes from reaching landing sites, thus preventing biting and the transition to the final gonotrophic phase.…”
Section: Mosquito Response To Bed Netsmentioning
confidence: 99%
“…Bed nets do, however, interfere with the landing portion of short-range phase by physically blocking mosquitoes from reaching landing sites, thus preventing biting and the transition to the final gonotrophic phase. Mosquito enter/ exit rates at net-occupied dwellings [37] suggest that there is a limit to the amount of time that mosquitoes will attempt to gain access to net-protected human hosts, after which they will abandon the effort and leave to find blood elsewhere.…”
Section: Mosquito Response To Bed Netsmentioning
confidence: 99%